The Academic Demoralization of Students in Online Learning During the COVID-19 Pandemic - Muassomah, Muassomah; Abdullah, Irwan; Hasanah, Umdatul; Dalmeri, Dalmeri; Sihombing, Adison Adrianus; Rodrigo, Luis (Frontiers in Education, 2022)
Academic moralization, which has been internalized through educational institutions with teacher supervision at schools, now falls into a decline in line with the implementation of distance education due to the coronavirus disease 2019 (COVID-19) pandemic. This article aims to show that an educational system that does not offer in-person teaching leads to students ignoring the values of academic morality, such as plagiarism, discipline, and responsibility. This article employs a qualitative descriptive method by relying on online news mapping data as a secondary source and verified data from interviews with elementary school students as the primary source. The results of this study indicate that online education as a learning solution during the pandemic has caused students to plagiarize, cheat, rely on others to complete their tasks, and lose an overall sense of discipline and responsibility. This study suggests a new direction of moral education that does not only rely on teacher supervision but rather builds the wisdom of students' independence upon learning.